Growing good : a beginner's guide to cultivating caring communities - Hemminger, William J. (Indiana University Press, 2021)
"Anger and hopelessness can overwhelm communities like weeds. So what can everyday people do to actually grow some good in their own hometown? Growing Good: A Beginner's Guide to Cultivating Caring Communities shows how ordinary people have transformed themselves into volunteers and activists. Centered mostly in the midwestern city of Evansville, Indiana, editor Bill Hemminger brings together the stories of normal people who have rolled up their sleeves and worked to make their community a better place by serving in food pantries, shelters, and schools. A teacher and his student started a native plant garden to help local insects thrive in a disused corner of their school property. A woman saw a billboard and was moved to become a voice for children in need. A professional photographer offered his services to people experiencing homelessness in order to help others witness their humanity. Hemminger also writes of his own extensive experience with community gardening to feed hungry neighbors. Filled with simple actions, clear steps, and useful lists, including how to care for and nurture your own inner peace and creativity, Growing Good will help readers of all ages plant seeds of hope and cultivate communities where everyone will thrive"--